Silicon particle
Patent Information
- Application Number
- JP2023134904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
AI Technical Summary
【0011】 本発明によれば、表面の酸化が抑制されたシリコン粒子が得られる。
Smart Images

Figure 2025029968000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to silicon particles. [Background technology]
[0002] Silicon (Si) particles are used in a variety of fields, including batteries, electronic devices, sensors, bio-medical applications, and semiconductors.
[0003] Lithium-ion secondary batteries are lightweight and have high capacity, so they are widely used as power sources for electronic devices such as mobile phones, and are also promising candidates for use as power sources in hybrid and electric vehicles.
[0004] Conventionally, graphite has been commonly used as the negative electrode material for lithium-ion secondary batteries, but there has been a limit to how much capacity can be increased. Therefore, it is expected that the capacity of lithium-ion secondary batteries can be increased by using Si, which has a theoretical capacity 10 times that of graphite, as the negative electrode active material.
[0005] When using a negative electrode active material made of Si, a large amount of lithium ions react with the active material, which allows for high capacity, but the volume change during charging and discharging is large. The volume change can cause cracks in the negative electrode active material, resulting in a decrease in the cycle characteristics of the lithium-ion secondary battery. As an effective solution to this problem, a technology to nanosize Si particles has been proposed.
[0006] Silicon nanoparticles have been attracting attention as a negative electrode material for high-energy density secondary batteries, but as the particle size becomes smaller, the specific surface area becomes larger, making the surface more susceptible to oxidation. The greater the amount of oxygen contained in the silicon nanoparticles, the greater the reaction between silicon oxide and lithium during charging and discharging, resulting in the generation of an irreversible Li2O phase, which reduces the capacity.
[0007] In Non-Patent Document 1, a Si 1-x O xThey prepared a lithium-ion battery and investigated the oxygen content dependence of its electrochemical properties, such as reversible and irreversible capacity, and reported that the higher the oxygen content, the smaller the reversible capacity. [Prior art documents] [Non-patent literature]
[0008] [Non-Patent Document 1] Z. Zhang et al. Energy Environ. Sci. 11, 1945 (2018) Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide silicon particles having surfaces that are inhibited from being oxidized. [Means for solving the problem]
[0010] The silicon particle according to the present invention is a silicon particle having a silicon core and a surface layer of a silicon oxide film, and the silicon oxide film has a Si-O4 coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) Peak area, Si-O2 coordination (Si 2 ) Peak area, Si-O3 coordination (Si 3 ) peak area, and Si-O4 coordination (Si 4 ) The ratio of the peak area to the total peak area is 0.2 or less. Effect of the Invention
[0011] According to the present invention, silicon particles having surfaces that are inhibited from being oxidized can be obtained. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram of a silicon particle. [Diagram 2] FIG. 1 is a diagram showing an example of peak fitting of an XPS spectrum. [Diagram 3] FIG. 1 is a schematic diagram showing a configuration of a silicon particle manufacturing apparatus. [Figure 4] This is a graph showing the Si4 peak area ratio to y in the average atomic composition SiOy of the silicon oxide film of the surface layer, together with the calculated values of the areas of the Si0 peak, Si1 peak, Si2 peak, Si3 peak, and Si4 peak, and the calculated value of the Si4 peak area ratio, calculated by the random bonding model (RBM). [Diagram 5] 1 is a graph showing the results of a charge / discharge test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0014] 1. Composition of silicon particles As shown in Fig. 1, silicon particle 1 has a silicon core 2 and a surface layer 3 of a silicon oxide film. Silicon particle 1 is a nanoparticle with an average particle size of less than 1000 nm. Observation of silicon particle 1 with a transmission electron microscope (TEM) has confirmed that central core 2 has a crystalline structure and surface layer 3 has an amorphous structure derived from oxidation.
[0015] The silicon oxide film of the surface layer 3 has a Si-O coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) Peak area, Si-O2 coordination (Si 2 ) Peak area, Si-O3 coordination (Si 3 ) peak area, and Si-O4 coordination (Si 4 ) Ratio of peak area to the total ("Si 4 / [Si 1 +Si 2 +Si 3 +Si 4 ]" or "Si4 The peak area ratio (also referred to as "peak area ratio") is 0.2 or less, and preferably 0.1 or less. Here, silicon oxide with Si-O4 coordination is SiO2, which is a stable silicon oxide, and four O (oxygen) atoms are coordinated around the Si atom, resulting in 4-coordination. Silicon oxide with Si-O1 coordination, silicon oxide with Si-O2 coordination, and silicon oxide with Si-O3 coordination are silicon oxides in intermediate oxidation states, and in each silicon oxide, one, two, and three O atoms are respectively coordinated around the Si atom, resulting in 1-coordination, 2-coordination, and 3-coordination, respectively.
[0016] The silicon particle 1 has a surface layer 3 of a silicon oxide film, and the surface layer 3 of the silicon oxide film is a Si 4 The peak area ratio is 0.2 or less, the proportion of silicon oxide with a low coordination number in the silicon oxide film of the surface layer 3 is high, and the oxygen content in the surface layer 3 is small. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, making it difficult for the irreversible Li2O phase to be generated, suppressing the irreversible capacity and providing a large reversible capacity.
[0017] Si-O4 coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) Peak area, Si-O2 coordination (Si 2 ) Peak area, Si-O3 coordination (Si 3 ) peak area, and Si-O4 coordination (Si 4 ) Ratio of peak area to the total (Si 4 The method for measuring the peak area ratio of Si (Si 0 ) peak, Si-O1 coordination (Si 1 ) peak, Si-O2 coordination (Si 2 ) peak, Si-O3 coordination (Si 3 ) peak, Si-O4 coordination (Si 4)Separate into peaks and calculate the area of each peak. Si 4 The peak area, Si 1 The peak area, Si 2 The peak area, Si 3 The peak area, Si 4 By dividing by the total of the peak areas, Si 4 The peak area ratio can be calculated. Figure 2 is a diagram showing an example of the peak intensity with respect to the binding energy after peak fitting. The thin solid line is the measurement data of the XPS spectrum, and the thick solid line and the broken line are the Si 0 peaks obtained by fitting, Si 1 peaks, Si 2 peaks, Si 3 peaks, Si 4 peaks. The peak near the binding energy of 99.3 eV is the Si 0 peak, and the peak near 100.4 eV is the Si 1 peak, and the peak near 101.4 eV is the Si 2 peak, and the peak near 102.5 eV is the Si 3 peak, and the peak near 103.5 eV is the Si 4 peak.
[0018] The average composition of the silicon oxide film of surface layer 3 will be described. The silicon oxide film of surface layer 3 is represented by SiOy where 0 < y ≤ 1.1. SiOy is the average atomic composition of surface layer 3, and the average atomic composition ratio y of O can be calculated by the following mathematical formula 1.
[0019]
Equation
[0020] Here, in the above mathematical formula 1, k is the Si - O coordination number, specifically 1, 2, 3, 4. Si k is the Si - Ok coordination (Si k ) peak area in the XPS spectrum measurement, the Si - O1 coordination (Si 1 ) peak area, the Si - O2 coordination (Si 2) Peak area, Si-O3 coordination (Si 3 ) Peak area, and Si-O4 coordination (Si 4 ) It is the ratio to the total of the peak areas. Specifically, Si k Peak area is divided by the sum of the Si 1 Peak area, Si 2 Peak area, Si 3 Peak area, Si 4 Peak areas.
[0021] When the silicon oxide film of the surface layer 3 of the silicon particle 1 is SiOy, the average atomic composition ratio y of O is 0 < y ≤ 1.1, and the atomic composition ratio of oxygen in the silicon oxide film of the surface layer 3 is small. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, it is difficult to generate the Li2O phase of the irreversible phase, the irreversible capacity can be suppressed, and a large reversible capacity can be obtained.
[0022] The thickness t of the silicon oxide film of the surface layer 3 shell will be described. The thickness t of the surface layer 3 shell is a value calculated from the average oxygen content in the silicon particle 1, the average particle diameter of the silicon particle 1, and the average atomic composition SiOy of the silicon oxide film of the surface layer 3 described above. The average oxygen content (mass%) in the silicon particle 1 is measured by an oxygen analyzer (EMGA-930 manufactured by Horiba, Ltd.). The average particle diameter of the silicon particle 1 is obtained by deriving the Si crystallite size by Rietveld analysis in X-ray diffraction (XRD; X-Ray Diffraction). The correlation between the particle diameter obtained from the crystallite size and the particle diameter obtained from TEM observation has been confirmed, and the validity of using the value obtained by deriving the Si crystallite size as the average particle diameter has been shown. t shell is calculated by creating an equation such that the value obtained by dividing the mass of O in the surface layer 3 by the sum of the mass of the core 2 and the mass of the surface layer 3 is the average oxygen content (mass%) in the silicon particle 1. The mass of the core 2 is the density of silicon (2.33 g / cm 3 ) multiplied by the volume of the core 2 (the radius is [average particle diameter / 2 - t shellIt is a value obtained by multiplying (the volume of the sphere). The mass of the surface layer 3 is a value obtained by multiplying the density of SiOy by the volume of the surface layer 3 (the volume obtained by subtracting the volume of the core 2 from the volume of a sphere with a radius of the average particle size / 2). Here, the density of SiOy is obtained from the density data at each oxidation amount of Si. The relationship between the oxidation amount of Si and the density may be measured in advance or existing data may be cited. As the existing data, for example, the values read from the graph of the oxidation amount and the density described in Fig. 7 of "F.G. Bell and L.Ley, PRB 37 (1988) 8383" are used. The mass of O in the surface layer 3 is a value obtained by multiplying the mass of the surface layer 3 by y / [1 + y] and the ratio of the atomic weight of O to the atomic weight of Si.
[0023] The thickness t of the surface layer 3 shell is preferably 1.0 nm or less, more preferably 0.5 nm or less. The silicon particles 1 have a Si 4 peak area ratio of 0.2 or less, a high ratio of low - coordinated silicon oxide in the silicon oxide film of the surface layer 3, a small oxygen content in the surface layer 3, and the thickness t shell of the surface layer 3 is as small as 1.0 nm or less. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, it is difficult to generate the irreversible - phase Li2O phase, the irreversible capacity can be suppressed, and a large reversible capacity can be obtained. Also, for the silicon particles 1, when the silicon oxide film of the surface layer 3 is SiOy, the average atomic composition ratio y of O satisfies 0 < y ≦ 1.1, the atomic composition ratio of oxygen in the silicon oxide film of the surface layer 3 is small, and the thickness t shell of the surface layer 3 is as small as 1.0 nm or less. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, it is difficult to generate the irreversible - phase Li2O phase, the irreversible capacity can be suppressed, and a large reversible capacity can be obtained.
[0024] The average particle size of the silicon particles 1 is preferably 150 nm or less, more preferably 80 nm or less. Since the average particle size is as small as 150 nm or less, the volume change during charge - discharge can be absorbed, so the cycle characteristics can also be improved.
[0025] 2. Manufacturing method of silicon particles A method for producing silicon particles 1 will be described. Silicon particles 1 can be produced by, for example, a high-frequency plasma spray method. In the high-frequency plasma spray method, nanoparticles are produced by supplying raw material to a high-temperature plasma (also called a plasma flame), completely evaporating the raw material to generate raw material gas, followed by rapid condensation of the raw material gas. The nanoparticles are rapidly cooled immediately after production, and oxidation is allowed to proceed while being rapidly cooled at a low temperature under an extremely low oxygen partial pressure, to obtain silicon particles 1 as nanoparticles in which oxidation is suppressed. A silicon oxide layer with a low coordination number can be formed by rapidly lowering the temperature range in which oxidation is likely to proceed by rapid cooling immediately after nanoparticle production.
[0026] An example of a silicon particle manufacturing apparatus that performs a high-frequency plasma spray method will be described with reference to Fig. 3. As shown in Fig. 3, the silicon particle manufacturing apparatus 10 includes a plasma torch 11, a raw material supply unit 12, a reaction vessel 13, a cooling unit 14, and a recovery unit 15.
[0027] The plasma torch 11 is provided in the reaction vessel 13. As the plasma torch 11, a direct current plasma torch, a high frequency plasma torch, a hybrid type plasma torch having a direct current plasma torch and a high frequency plasma torch, etc. can be used. In this embodiment, a hybrid type plasma torch is used as the plasma torch 11.
[0028] Although not shown, the plasma torch 11 is connected to a power source, a working gas supply unit, etc. The plasma torch 11 receives working gas from the working gas supply unit and current and voltage from the power source, thereby converting the working gas into plasma and generating a high-temperature plasma flame 16. As the working gas, for example, a mixed gas of Ar gas and H2 gas is used.
[0029] The plasma flame 16 is introduced into the reaction vessel 13. The temperature of the plasma flame 16 decreases from the generation part 17 of the plasma flame 16 toward the tail flame part 18. The generation part 17 of the plasma flame 16 has a temperature range equal to or higher than the boiling point of the powder raw material 20 described later.
[0030] The raw material supply unit 12 is provided in the plasma torch 11. The raw material supply unit 12 supplies the powder raw material 20 containing elements constituting nanoparticles to the plasma flame 16. When the raw material 20 is supplied from the raw material supply unit 12 to the plasma flame 16, the raw material 20 is vaporized and a raw material gas 21 is generated. The supply rate of the raw material 20 supplied to the plasma flame 16 per unit time is preferably 25 g / min or less, more preferably 17 g / min or less. By reducing the supply rate, the concentration of silicon vapor is reduced, and the average particle size of the silicon particles 1 can be reduced. In the raw material supply unit 12, when supplying the powder raw material 20 to the plasma flame 16, for example, Ar gas, a mixed gas of Ar gas and H2 gas, or the like may be used as a carrier gas. In this embodiment, Ar gas is used as the carrier gas.
[0031] Metallic Si is used as the raw material 20. The diameter (grain size) of the powder raw material 20 is preferably 0.1 μm or more and 100 μm or less.
[0032] The reaction vessel 13 has an upper portion 13a, a lower portion 13b provided so as to face the upper portion 13a, and a side portion 13c connecting the upper portion 13a and the lower portion 13b. The upper portion 13a is provided with a plasma torch 11. The side portion 13c is provided with an opening to which the cooling unit 14 is connected. In this embodiment, a mixed gas of Ar gas and H2 gas as a working gas of the plasma torch 11 and Ar gas as a carrier gas of the raw material supply unit 12 are introduced into the reaction vessel 13. The temperature of the plasma flame 16 introduced into the reaction vessel 13 decreases from the upper portion 13a to the lower portion 13b of the reaction vessel 13. The pressure inside the reaction vessel 13 during the generation of the plasma flame 16 is controlled to, for example, 20.0 kPa to 104.0 kPa (150 Torr to 780 Torr). The temperature T1 of the lower portion 13b is, for example, 1000°C or less.
[0033] A plasma flame 16 is introduced into the reaction vessel 13, and a source gas 21 is generated in the plasma flame 16. The source gas 21 moves from the generation section 17 to the tail flame section 18 along the flow of the plasma flame 16, and is cooled as it moves. In the process of cooling, the source gas 21 is rapidly condensed and silicon particles 1 are generated. The temperature Tg of the region ER immediately after the condensation / nanoparticle formation field in the plasma flame 16 is 1500°C to 2500°C. In the reaction vessel 13, a gas flow 23 of the source gas 21 containing the silicon particles 1 is generated. The gas flow 23 flows from an opening provided in the side section 13c to the cooling section 14.
[0034] The oxygen concentration in the reaction vessel 13 during the generation of the plasma flame 16 (high temperature plasma) is 1000 ppm or less, preferably 100 ppm or less, and more preferably 10 ppm or less. The oxygen partial pressure is the pressure in the reaction vessel 13 during the generation of the plasma flame 16 multiplied by the oxygen concentration. When the pressure in the reaction vessel 13 is 30 kPa, the oxygen partial pressure is 30 Pa or less, preferably 3 Pa or less, and more preferably 0.3 Pa or less. In the reaction vessel 13 of this embodiment, a mixed gas of Ar gas and H2 gas is introduced, and oxygen gas for the purpose of oxidizing the surface of the silicon particle 1 is not introduced. The oxygen present in the reaction vessel 13 during the generation of the plasma flame 16 is oxygen mixed in the Ar gas as an inevitable impurity.
[0035] The cooling section 14 is provided between the reaction vessel 13 and the recovery section 15. The cooling section 14 is composed of a heat exchanger such as a radiator. The cooling section 14 has an inlet 14a connected to the reaction vessel 13 and an outlet 14b connected to the recovery section 15. The temperature of the inlet 14a of the cooling section 14 is 1500°C to 2500°C, similar to the temperature Tg of the region ER immediately after the condensation / nanoparticle formation field in the plasma flame 16.
[0036] The cooling section 14 cools the temperature of the gas flow 23 (raw material gas 21) introduced from the reaction vessel 13 to a temperature below the heat-resistant temperature of the recovery section 15. The gas flow 23 cooled by the cooling section 14 is led to the recovery section 15 from the outlet 14b. In the cooling section 14, rapid oxidation of the silicon particles 1 progresses, and silicon particles 1 with suppressed oxidation are obtained. The temperature T2 of the outlet 14b of the cooling section 14 is 180°C or less, preferably 120°C or less, and more preferably 60°C or less. The temperature difference Tg-T2 between the temperature Tg of the region ER immediately after the condensation / nanoparticle formation field in the plasma flame 16 and the temperature T2 of the outlet 14b of the cooling section 14 is 1320°C to 2440°C. When the time from when the gas flow 23 enters the inlet 14a of the cooling section 14 to when it leaves the outlet 14b is defined as the cooling time t, this cooling time t is 80ms to 200ms. The temperature difference Tg-T2 divided by the cooling time t ([Tg-T2] / t) is 6.6×10 3℃ / sec~30.5×10 3 °C / sec. Here, for wafer-sized silicon, the oxidation reaction constant increases exponentially with increasing temperature at oxidation temperatures of 1200K (927°C) or higher, but oxidation hardly progresses at temperatures below 1200K (927°C). It is believed that micron-sized silicon particles also behave in a similar manner to wafer-sized silicon. In contrast, for nano-sized silicon particles, the temperature range at which oxidation progresses expands to the lower temperature side, up to about 900K (627°C), and oxidation progresses even at lower temperatures. By rapidly lowering the temperature of nano-sized silicon particles generated in a high-temperature environment to 900K or lower, it is possible to suppress oxidation even in nano-sized silicon particles (a state in which oxidation progresses very slowly). The gas flow 23 (raw material gas 21) introduced from the reaction vessel 13 was 6.6×10 3 ℃ / sec~30.5×10 3 Cooling at a cooling rate of °C / sec is called "ultra-quenching." The cooling unit 14, which serves as a heat exchanger for ultra-quenching, can ultra-quench the raw material gas 21 from temperature Tg to temperature T2, thereby lowering the temperature below 900K (627°C), the temperature range at which oxidation of nano-sized silicon particles progresses, in a short cooling time t of 80 ms to 200 ms.
[0037] 3 is a radiator having a straight pipe 26 that rectifies the flow of the gas flow 23 containing the silicon particles 1 in one direction, and a refrigerant pipe 27 through which a refrigerant 28 flows. The temperature of the refrigerant 28 is, for example, 30° C. In the silicon particle manufacturing apparatus 10, the cooling unit 14 rectifies and ultra-rapidly cools the gas flow 23 containing the silicon particles 1.
[0038] The collection unit 15 is introduced with the gas flow 23 cooled by the cooling unit 14, and collects the silicon particles 1 contained in the gas flow 23. The collection unit 15 is connected to an exhaust unit 29 constituted by a vacuum pump or the like, and is configured to exhaust the gas flow 23.
[0039] 3. Action and Effects The silicon particles 1 have an Si peak area ratio measured by XPS of the silicon oxide film of the surface layer 3 4 of 0.2 or less, a high proportion of silicon oxide with a low coordination number in the silicon oxide film of the surface layer 3, and a small oxygen content in the surface layer 3. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, it is difficult to form an irreversible Li2O phase, the irreversible capacity can be suppressed, and a large reversible capacity can be obtained. Further, when the silicon oxide film of the surface layer 3 is SiOy, the silicon particles 1 have an average atomic composition ratio y of O such that 0 < y ≤ 1.1, and the atomic composition ratio of oxygen in the silicon oxide film of the surface layer 3 is small. Therefore, the amount of oxygen reacting with lithium in the surface layer 3 is small, it is difficult to form an irreversible Li2O phase, the irreversible capacity can be suppressed, and a large reversible capacity can be obtained.
[0040] The silicon particles 1 have an Si peak area ratio measured by XPS of the silicon oxide film of the surface layer 3 4 of 0.1 or less, whereby the proportion of silicon oxide with a low coordination number in the silicon oxide film of the surface layer 3 is higher and the oxygen content in the surface layer 3 is smaller, so that a larger reversible capacity can be obtained.
[0041] Since the silicon particles 1 have an average particle diameter of 150 nm or less, they can absorb volume changes during charge and discharge, so that the cycle characteristics can be improved.
[0042] The silicon particles 1 have a surface layer 3 with a high proportion of silicon oxide with a low coordination number formed on the surface of the silicon core 2. For this reason, the silicon particles 1 taken out from the recovery unit 15 into the atmosphere do not undergo oxidation even in the atmosphere. shell Since the thickness t of the surface layer 3 is 1.0 nm or less, the oxygen content in the surface layer 3 is smaller, so that a larger reversible capacity can be obtained.
[0043] The silicon particles 1 have a surface layer 3 with a high proportion of silicon oxide with a low coordination number formed on the surface of the silicon core 2. Therefore, the silicon particles 1 taken out from the recovery unit 15 into the atmosphere do not undergo oxidation even in the atmosphere.
[0044] 4. Examples (1) Silicon particles Seven types of silicon particles were produced using the plasma spray method, and were designated as samples 1 to 5, 7, and 8. Samples 2, 4, and 5 are silicon particles obtained by using the silicon particle production apparatus 10 described in the embodiment and quenching the raw material gas 21 from temperature Tg to temperature T2 with the cooling unit 14 (ultra-quenching heat exchanger) as a radiator. The pressure in the reaction vessel 13 during the generation of the plasma flame 16 was set to 30 kPa. Since a general grade (99.99%) Ar gas was used, the oxygen concentration (oxygen partial pressure) in the reaction vessel 13 during the generation of the plasma flame 16 was 100 ppm (3 Pa) or less, which is an unavoidable mixture. The temperature Tg was set to approximately 1500°C at which Si nucleates. The temperature T2 was 30°C, which is the same as the temperature of the refrigerant 28. The cooling time t was set to 120 ms. Therefore, [Tg-T2] / t was 12.3×10 3 °C / sec. Samples 1, 3, 7, and 8 are silicon particles obtained by providing a water-cooled collection container using water at 30°C as a refrigerant in the lower portion 13b of the reaction container 13 instead of the cooling section 14 of the silicon particle production apparatus 10, and cooling the raw material gas 21 with the water-cooled collection container. The pressure, oxygen concentration (oxygen partial pressure), and temperature Tg in the reaction container 13 during generation of the plasma flame 16 were the same as those of Samples 2, 4, and 5. In Samples 1 to 5, 7, and 8, the average particle size was changed by changing the supply rate (g / min) of the powder raw material 20.
[0045] Sample 9 is silicon particles that have been forcibly oxidized by wet oxidation in a wet oxygen atmosphere at 500°C for 20 minutes, compared to the silicon particles in Sample 4. Sample 6 is commercially available silicon nanoparticles (100 nm (Si purity 99) manufactured by Japan NER Co., Ltd.).
[0046] Table 1 summarizes the composition and manufacturing conditions of each sample.
[0047] [Table 1]
[0048] The "average grain size" in Table 1 is the average grain size obtained by deriving the Si crystallite size by Rietveld analysis in X-ray diffraction (XRD), as described in the embodiment. "y in SiOy" is the average atomic composition ratio y of O in the average atomic composition SiOy of the silicon oxide film of the surface layer 3, calculated by the above formula 1. "Si 4 The "peak area ratio" is the ratio of the Si-O4 coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) Peak area, Si-O2 coordination (Si 2 ) Peak area, Si-O3 coordination (Si 3 ) peak area, and Si-O4 coordination (Si 4 ) is the ratio to the total peak area. "Oxide film thickness" is the thickness t shell As described in the embodiment, it was calculated from the average oxygen content in the silicon particles, the average particle size of the silicon particles, and the average atomic composition of the silicon oxide film, SiOy.
[0049] Comparing Samples 1, 3, 7, and 8, in which the source gas 21 was cooled using a water-cooled collection vessel, the average particle size became smaller and the particles were classified into "y in SiOy" and "Si 4 It can be seen that there is a tendency for the "peak area ratio" to increase. As the particle size decreases, the specific surface area increases, and it is believed that this increases the area that can come into contact with oxygen, making oxidation more likely to occur. Nevertheless, due to the effect of oxidation progressing under low oxygen partial pressure, in sample 3 with an average particle size of more than 150 nm, the average atomic composition ratio y of O in the average atomic composition SiOy of the silicon oxide film in the surface layer 3 is 1.1 or less, and 4 The obtained silicon particles had a peak area ratio of 0.2 or less, which means that oxidation of the surface was suppressed. This is thought to be because the temperature range in which oxidation is likely to proceed shifts to the higher side due to the large average particle size, and as a result, the temperature falls below this range in a short period of time. In samples 2, 4, and 5, in which the raw material gas 21 was cooled by the cooling unit 14 as a heat exchanger for ultra-rapid cooling, the average grain size was as small as 150 nm or less (particularly in samples 4 and 5, the average grain size was about 20 nm to 40 nm), but the average atomic composition ratio y of O in the average atomic composition SiOy of the silicon oxide film of the surface layer 3 was 1.1 or less, and Si 4 The peak area ratio was 0.2 or less and 0.1 or less, confirming that the silicon particles had very little surface oxidation. This is believed to be due to the oxidation proceeding under low oxygen partial pressure and when rapidly cooled to a low temperature. The forcedly oxidized silicon particles in sample 9 and the commercially available silicon nanoparticles in sample 6 are shown in Fig. 1. 4 The peak area ratio is larger than that of samples 1, 3, 7, and 8 with similar average particle size, confirming that surface oxidation has progressed.
[0050] In Fig. 4, the horizontal axis represents y in the average atomic composition SiOy of the silicon oxide film on the surface layer, and the vertical axis represents Si 4 The peak area ratios of Si to y in SiOy for samples 1 to 9 are 4 The graph shows the peak area ratios calculated using the random-bonding model (RBM). 0 Peak, Si 1 Peak, Si 2 Peak, Si 3 Peak, Si 4 The calculated peak area curve is also shown. The graph also shows the Si 1 Peak, Si 2 Peak, Si 3 Peak, Si 4 Si, calculated from the peak area 4 The calculated peak area ratio curve is also 4 / Si 1~4 is shown as:
[0051] In Fig. 4, the Si 4 The peak area ratio plot is the Si peak area ratio plot by RBM. 4 The curve of the calculated peak area ratio is closer to Si 4 It can be seen that the peak area ratio is on the smaller side. Here, it has been confirmed that the initial oxidation process of Si changes the thickness stepwise, at least on the clean surface of the Si wafer, and it is thought to correspond to Herman's oxidation structure, in which the bonds in the oxide layer change gradually from Si-O1 coordination to Si-O2 coordination, Si-O3 coordination, and Si-O4 coordination. From the plots of samples 2, 4, and 5, it can be seen that under typical oxidation conditions, oxidation progresses to about the theoretical value and Si-O4 coordination bonds are formed, whereas oxidation under low temperature and low oxygen partial pressure clearly suppresses the Si-O4 coordination ratio below the theoretical value.
[0052] (2) Battery characteristics Negative electrodes were produced using the silicon particles of each of Samples 1, 5, and 9, and a charge / discharge test was performed on each negative electrode using an electrochemical cell.
[0053] The method of producing the negative electrode will be described. A slurry containing silicon particles was applied onto a negative electrode current collector, and the negative electrode was produced by drying and pressing. The slurry was produced by mixing silicon particles, a binder material for the negative electrode, and a conductive assistant, and adding an appropriate amount of solvent to this mixture. Polyimide was used as the binder material for the negative electrode, carbon black as the conductive assistant, and NMP as the solvent. The mixture was 60 wt% silicon particles, 25 wt% binder material for the negative electrode, and 15 wt% conductive assistant. The slurry was applied in a film form by the doctor blade method onto a negative electrode current collector formed of Cu (copper) foil with a thickness of 12 μm. The thickness of the coating film was 75 μm. The coating film was dried under air. The coating film was then pressed with 10 kN. The thickness of the coating film after pressing was about 10 μm. In this way, negative electrodes using the silicon particles of Sample 5, Sample 1, and Sample 9 were produced.
[0054] The electrochemical cell used lithium metal foil as the negative counter electrode. The electrolyte was a solution of ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate mixed in a volume ratio of 1:1:0.2, with 1.0 mol / L LiPF6 dissolved in it. Charge and discharge were performed at a constant current of 0.1 mA (0.02 C) for cycles 1 to 3, and at a constant current of 0.5 mA (0.1 C) for cycles 4 to 100. The cutoff voltage was set to 0 to 1.5 V. The results of the charge and discharge test are shown in Figure 5. The horizontal axis shows the number of cycles, and the vertical axis shows the charge and discharge capacity. The open marks show the charge capacity, and the filled marks show the discharge capacity.
[0055] FIG. 5 confirms that Sample 5 has a higher initial capacity than Sample 1 and Sample 9, and maintains a high capacity up to 50 cycles. [Explanation of symbols]
[0056] 1 Silicon Particle 2 cores 3 Surface layer 10. Silicon particle manufacturing equipment 11 Plasma Torch 12 Raw material supply department 13 Reaction vessel 14 Cooling section 15 Collection Department 16 Plasma Flame 20 raw materials 21 Raw gas 23 Gas Flow Region immediately after the condensation and nanoparticle formation field in an ER plasma flame
Claims
1. A silicon particle having a silicon core and a silicon oxide surface layer, The silicon oxide film has a Si—O coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) peak area, Si—O2 coordination (Si 2 ) peak area, Si—O3 coordination (Si 3 ) peak area, and Si—O4 coordination (Si 4 ) The ratio of the peak area to the total peak area is 0.2 or less. Silicon particles.
2. A silicon particle having a silicon core and a silicon oxide surface layer, The silicon oxide film is SiOy, where 0<y≦1.
1. Silicon particles.
3. The silicon oxide film has a Si—O coordination (Si 4 ) peak area, Si-O1 coordination (Si 1 ) peak area, Si—O2 coordination (Si 2 ) peak area, Si—O3 coordination (Si 3 ) peak area, and Si—O4 coordination (Si 4 ) The ratio of the peak area to the total peak area is 0.1 or less.
3. Silicon particles according to claim 1 or 2.
4. The average particle size is 150 nm or less.
3. Silicon particles according to claim 1 or 2.
5. The thickness of the surface layer is 1.0 nm or less.
3. Silicon particles according to claim 1 or 2.